Reinventing alterity: the woman and the albino in Takadini’s subtext - Tagwirei, Cuthbeth (2016)
This paper discusses the folly of cultural representation with specific reference to Ben Hanson’s Takadini. Focus is on the import that Takadini is an advocate for the acceptance of marginalized groups such as women and albinos. Indeed, the text raises awareness to the problems women and albinos face in an African patriarchal societies and how much they struggle to ameliorate their problems. The researcher argues that Takadini fails dismally in what its author sets out to do: reinscribing the woman and the albino into society. Instead, the subtext is a reworking of alterity. It is a reworking of alterity in the sense that both the woman, Sekai, and the albino, Takadini, remain at the fringes of society. While it might be tempting to excuse such a representation on the basis that the author was attempting to recreate the sentiments of primitive societies whose belief systems were informed by patriarchy and superstition, it should not escape the reader that Hanson is complicit to the overall sentiments discernible in Takadini. In his legitimation, Hanson acknowledges his friends for the ‘success’ of his project, “especially Dr. John Makumbe, who read the manuscript and loved it” (4). The assumption seems to be that if Dr. Makumbe, who is an albino himself, loved it then it must be an authentic representation of albinos. The paper explores how Hanson, who is neither a woman nor an albino, ventures to re-inscribe the two margins and succeeds principally in re-inventing their otherness. The researcher contents that for a text published in 1997 in a more tolerant era, Takadini is a betrayal of both the woman and the albino in their quest for humanness.